Technology, Size, and Organizational Structure: A Reexamination of the Okayama Study Data - Singh, Jitendra V. (Academy of Management Journal, 1986)
In this article the author reexamines data from a study that focused on the effects that technology and size have on organizational structure. The study, known as the Oklahoma Study, obtained data from 50 Japanese factories and found that size affected the areas of structural differentiation and formalization to a greater degree than technology; however, technology was responsible for affecting all of the other areas examined such as labor inputs, cybernetic complexity, cost, wages and differentiation of management from ownership. In this reexamination, the author attempts to clear up areas of confusion in the original research.